Lifelong Learning Development and Policy in Lithuania - Mickūnaitė, Elena (Acta Paedagogica Vilnensia, 2004)
The major focus in this work is on learning and education continuity for adults. The actuality of this research lies in the fact that lifelong learning being the main principle of European education and development policy, on Lithuanian accession there is a rapid change of educational documents and legislation and their adjustment according to European education criteria. For this reason the goal of this research is to survey the development of the lifelong learning idea in the Lithuanian laws, concepts and initiatives. The methodology of the research is based on the method of document analysis and lifelong learning concept. The survey of the present educational legislation, strategies and initiatives leads to certain critical conclusions.
Keywords: lifelong learning; adult learning; education legislation; educational policy